Vegetation structure and carbon storage of a coffee-based agroforestry system in a chinantec community in Oaxaca - Toribio-Ferrer , Luis Miguel (2025)
The objective of this study was to evaluate the structure and carbon storage in a coffee agroforestry system in the Chinantec community of Santiago Tlatepusco, Oaxaca. A census was conducted in a one-hectare plot, evaluating all woody species and coffee plants, and measuring height, diameters, and coverage. The horizontal structure was analyzed using the Importance Value Index (IVI), and the stored dry biomass and carbon were quantified using specific equations. A total of 311 woody individuals were recorded, distributed among 27 species and 15 families, with Theobroma cacao and Citrus sinensis standing out for their abundance and dominance. The total coverage of the agroforestry system was 87,18 %. The total stored carbon content was 19,710 MgC ha⁻¹, with a significant contribution from the coffee plants (9,162 MgC ha⁻¹) and timber species such as Cedrela odorata (2,871 MgC ha⁻¹). The IVI showed that Theobroma cacao and Citrus sinensis are the most important species in the system. It was concluded that the evaluated coffee agroforestry system represents a sustainable production model with significant potential for carbon capture and biodiversity conservation, contributing to the socioeconomic development of the community.